Linking Employee Engagement To Employee Value Proposition: Insight From Faculty Of Administrative Science Universitas Indonesia: Linking Employee Engagement To Employee Value Proposition: Insight From Faculty Of Administrative Science Universitas Indonesia - Soeling, Pantius Drahen; Ramaditya, Muhammad; Parastry, Annisa; Oktafia, Evie (International Journal of Business Studies, 2024)
This study is aims to examine the role of employee value proposition towards employee engagement at faculty administrative science Universitas Indonesia. Lecturers and academic staff are human resources who play an important role in improving student education and achievement and are also one of the key components of the education system in higher education. The object of research is private university lecturers and academic staff. By distributing questionnaires as research for data collection. This research used 117 respondents from lectures and academic staff. The sampling technique was purposive sampling. The analysis tool used is the descriptive and inferential with SPSS 23. The research results show that employee value proposition have positive and significance effect towards employee engangement. Fulfillment of the employee value proposition results in stable and group employee engagement dedicated employees, as well as an environment with an innovative mindset and performance improvement can also be influenced by a committed workforce.